2004
DOI: 10.1080/11250000409356560
|View full text |Cite
|
Sign up to set email alerts
|

Osteological and molecular analysis of three Sicilian populations ofAphanius fasciatus(Teleostei, Cyprinodontidae)

Abstract: The study of three Sicilian populations of Aphanius fasciatus was carried out by examining the mitochondrial control region and the morphology of the bony elements of the skull and vertebral column. The osteological and molecular data obtained indicate a marked differentiation between the populations examined resulting from their isolation, even if the dendrograms of the two approaches are dissimilar. Molecular investigations show that populations are characterized by haplotypes that are well defined in relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Although the two segments used exhibit different mutation rates, with 16S rRNA being more conserved than D-loop, the results obtained were consistent between the two markers and with the existing literature (Tigano et al 2004(Tigano et al , 2006Rocco et al 2007;Triantafyllidis et al 2007;Pappalardo et al 2008;Annabi et al 2012Annabi et al , 2013Ferrito et al 2013;Buj et al 2015). Only Hrbek and Meyer (2003) maintained that signs of genetic structuring of A. fasciatus across the Mediterranean Sea would have been diluted by subsequent gene flow.…”
Section: Mediterranean Seasupporting
confidence: 79%
See 2 more Smart Citations
“…Although the two segments used exhibit different mutation rates, with 16S rRNA being more conserved than D-loop, the results obtained were consistent between the two markers and with the existing literature (Tigano et al 2004(Tigano et al , 2006Rocco et al 2007;Triantafyllidis et al 2007;Pappalardo et al 2008;Annabi et al 2012Annabi et al , 2013Ferrito et al 2013;Buj et al 2015). Only Hrbek and Meyer (2003) maintained that signs of genetic structuring of A. fasciatus across the Mediterranean Sea would have been diluted by subsequent gene flow.…”
Section: Mediterranean Seasupporting
confidence: 79%
“…Two segments of mtDNA were then amplified for each individual: the first (780 bp) comprised a fragment of the 16S rRNA, while the second (339 bp) was a section of the mitochondrial control region (D-loop). The conditions for amplification were as follows: for 16S, 30 cycles of amplification were performed with denaturation at 94°C for 35 s, annealing at 52°C for 35 s and extension at 72°C for 120 s; for D-loop, 35 cycles of amplification were used with denaturation at 94°C for 30 s, annealing at 51°C for 30 s and extension at 72°C for 40 s. For the 16S segment primers L3002 and H4280 were used (Hrbek & Meyer 2003), whereas for the D-loop segment the forward primer designed by Tigano et al (2004) and the reverse primer designed by Meyer et al (1990) were used. The amplified fragments were then sent out for sequencing at the VBC Biotech Service GmbH (Austria).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of this genus mostly inhabit springs, swamps or lakes with warm water, or saline to hypersaline conditions (Alcaraz and Garcı´a-Berthou, 2007;Kottelat and Freyhoff, 2007;Alcaraz et al, 2008a,b). The populations of the non-endemic species A. faciatus are morphologically and genetically well differentiated (Cimmaruta et al, 2003;Tigano et al, 2004;Ferrito et al, 2007). The populations of the non-endemic species A. faciatus are morphologically and genetically well differentiated (Cimmaruta et al, 2003;Tigano et al, 2004;Ferrito et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A. fasciatus therefore serves as model organism in many studies on genetic structures and levels of differentiation based on different methods, i.e. osteological characters (Tigano et al 1999, Ferrito et al 2003, genetic data (Hrbek and Meyer 2003, Triantafyllidis et al 2007, Pappalardo et al 2008, both osteological and genetic data , Tigano et al 2004, and otoliths (Reichenbacher et al 2007). These studies have revealed that A. fasciatus from Italy, Greece and Northern Tunisia is genetically structured by geographic isolation and that a clear link exists between genetic structures and the Pleistocene history of the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%